EVALUATION OF EDUCATIONAL ASSISTANCE THROUGH THE INDONESIA PINTAR PROGRAM IN PEKANBARU STATE ELEMENTARY SCHOOLS - Raifita, Raifita; Zarkasih, Zarkasih; Sapriati, Amalia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
The Indonesia Smart Program (PIP) is designed to assist school-age children from poor or vulnerable families in continuing their education until completion of secondary education, both through formal and non-formal education channels. Through this program, the government seeks to prevent students from the possibility of dropping out of school, and it is hoped that it can attract dropouts to resume their education. This research aims to evaluate the effectiveness of educational assistance through the Indonesia Smart Program in Pekanbaru State Elementary Schools. The research method uses a qualitative descriptive approach, employing the policy evaluation model by Dunn. The policy evaluation model used in the research is formal evaluation. The subjects of this study are students receiving assistance from the Indonesia Smart Program, and the research object is the evaluation of the implementation of the Indonesia Smart Program at State Elementary Schools 95, 84, and 44 in the Tenayan Raya District of Pekanbaru. Data analysis techniques in this study are carried out through three activities: data reduction, data presentation, and drawing conclusions. The research results show that the effectiveness of educational assistance in the form of PIP in State Elementary Schools 95, 84, and 44 in the Tenayan Raya District of Pekanbaru is quite effective. This includes the screening of target groups, the intended use of assistance, the timeliness of assistance distribution, and the utilization of educational assistance through the Indonesia Smart Program